Qualidade pós-colheita de gérberas vermelhas em função da temperatura de armazenamento - Muniz, Ana Carolina Corrêa [UNESP]; Galati, Vanessa Cury [UNESP]; Marques, Kelly Magalhães [UNESP]; Mattiuz, Claudia Fabrino Machado; Mattiuz, Ben-Hur [UNESP] (FapUNIFESP (SciELO), 2016)
This study aimed to verify the best storage temperature in the postharvest quality conservation of inflorescences of gerberas cv. ‘Intenza’. Inflorescences were kept in distilled water and stored at the temperatures of 22°C (control); 12°C; 8°C and 4°C. The experiment was conducted in a completely randomized design in split plot with two factors: 4 treatments (temperatures) X 4 evaluation dates (0, 3, 6 and 9 days). It was used three replicates, with three inflorescences each. It were evaluated the variation of fresh mass, relative water content, soluble and reducing sugars content and longevity. Results were submitted to analysis of variance and means compared by Tukey test at 5% of probability. The inflorescences of gerbera maintained at 4°C, 8°C and 12°C showed a greater postharvest life compared with the inflorescences of the control, highlighting those kept at 4°C which presented less loss of mass and higher soluble sugar content; thus, maintaining the quality of gerberas for a longer period, with vase life of approximately 15 days.
Postharvest quality of red gerberas depending on the storage temperature
Keywords: Carbohydrates; Cut flowers; Floral longevity; Gerbera Jamesonii L.